Analysis of Socio-Demographic and Access-Related Factors Associated With Condom Use Among Female Sex Workers - Eklesia Putri Doda; Angela Fitriani Clementine Kalesaran; Afnal Asrifuddin (Jurnal Ilmu Kesehatan Masyarakat, 2025)
Manado City recorded the highest number of HIV/AIDS cases in North Sulawesi in 2023, with 1,027 HIV cases and 1,128 AIDS cases. Female Sex Workers (FSWs) are considered a high-risk group for infection. One of the simplest ways to prevent HIV/AIDS transmission among FSWs is by using condoms during sexual intercourse. The objective of this study was to analyze factors associated with condom use in HIV/AIDS prevention among FSWs in Manado City. This was a quantitative research using an analytical survey method with a cross-sectional study approach. The sample consisted of 108 respondents selected using a purposive sampling technique, and the research instrument employed was a questionnaire. The result of bivariate analysis using the chi-square test shows that education (p = 0.027), age at becoming as female sex worker (p = 0.026), and condom availability (p = 0.000) are significantly associated with condom use among female sex workers. The result of multivariate analysis shows that the dominant factors influencing condom use were education (exp(B) = 4.249) which means that education has a 4.249 times greater influence on the likelihood of condom use, indicating that individuals with higher education tend to use condoms more often and condom availability (exp(B) = 51.582) which means that condom availability has a 51.582 times greater effect on the likelihood of condom use, indicating that better access to condoms significantly increases the likelihood of their use. The results of this study can be used by North Sulawesi Indonesia Family Planning Association and related institutions to design more effective intervention programmes, consistently increase condom availability and educate people about the benefits of condom use.